O dramatycznej fazie rozwojowej pansomatyzmu Kotarbińskiego - Lejewski, Czesław (Filozofia Nauki, 1994)
As the author sees it, Tadeusz Kotarbiński's reism is an ontology with semantical ramifications. Contrary to Kazimierz Ajdukiewicz's view the reist is not commited to any particular categorially determined language; he has to use, and is at liberty to do so, the language of whoever happens to be his opponent always provide that it is a categorially determined language. Contrary to Ajdukiewicz's opinion, the positive ontological thesis of resim (i.e. the thesis that for all a and b, if a is a b, then a is bulky and lasting) is not a tautology; it is a denial of the thesis held by unicategorial Platonism. Contrary to Ajdukiewicz's insistence, the negative ontological thesis of reism (i.e. the thesis that there are no properties, there are no relations, there are no events, etc.) consists of propositions which, in the light of multicategorial idealization of ordinary language, are meaningful and syntactically well constructed. They deny equally meaningful and syntactically well constructed assertions of multicategorial Platonism.